Principles of embodied pedagogy: The role of the drama educator in transforming student understanding through a collaborative and embodied aesthetic practice. Issue 1 (1st August 2019) - Bird, Jane; Sinclair, Christine
When undertaking teaching as an embodied pedagogy, the teacher understands the body as a site of risk and possibility as well as a site of knowing – of self, of others (empathy) and of the world. This article focuses on research undertaken by the authors in the International Centre for Classroom Research at the University of Melbourne into the pedagogical and creative learning practices associated with an embodied approach to teaching, and draws on a growing body of research undertaken by cognitive scientists investigating the role of the body in thinking, learning and problem-solving (Glenberg 2008), and by drama education researchers into the ways that embodiment can substantially enhance learning (Ewing 2010). The authors contend that researchers have focused principally on the processes and characteristics of embodied learning and have given less attention to the pedagogical practices employed by drama educators as facilitators of embodied learning. This article addresses this gap in the research by examining the role of the drama educator in facilitating the conditions for aesthetic embodied learning experiences in a classroom environment. The authors propose a set of principles of embodied pedagogies for implementation in and beyond the drama classroom.